Ca(2+)- and CaMKII-mediated processes in early LTP - Byth, Lachlan A (Ann Neurosci, 2014)
Learning methods determine the degree of stimulation of engrams encoding information to be memorised. More enriching modes of learning allow more enduring long-term potentiation of the synapses associated with these memories. The additional activity causes a prolonged increase in [Ca2+] in the dendritic spine of the postsynaptic neuron. This allows Ca(2+)-mediated molecular pathways to bring about cytoskeletal remodeling, posttranslational modifications, and protein trafficking. These processes contribute to early long-term potentiation of the synapses, strengthening the memory they store and lead to improved performance on tests of memory recall.